Mulyawan Karim (2021), "Di rumah panjang; Pergulatan hidup dan cinta orang Dayak Iban" - Lumenta, Dave (Wacana, Journal of the Humanities of Indonesia, 2023)
This is a book review of Di Rumah Panjang: Pergulatan Hidup dan Cinta Orang Dayak Iban authored by journalist-anthropologist Mulyawan Karim. This is a popularly-written ethnographic account on the Iban of West Kalimantan based on the author's travels in 1993/94 and 2018. As the body of literature on the Iban on the Indonesian side is generally small, this monograph is the first of its kind written in Indonesian. What Mulyawan Karim has achieved in thematically positioning his book is in exploring personal life struggles and even love stories, two important themes of everyday life that are arguably absent from the general focus of published monographs in Borneo studies on development, social transformation, environmental change and politics.